2012
DOI: 10.1002/pen.23276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment of carbon nanofibers on the electromagnetic shielding effectiveness of linear low density polyethylene nanocomposites

Abstract: The electrical properties and electromagnetic shielding effectiveness (EM SE) of nanocomposites consisting of heat‐treated carbon nanofibers (Pyrograf® III PR‐19, CNF) in a linear low density polyethylene (LLDPE) matrix were assessed. Heat treatment (HT) of carbon nanofibers at 2500°C significantly improved their graphitic crystallinity and intrinsic transport properties, thereby increasing the EM SE of the nanocomposites. Nanocomposites containing 11 vol% (20 wt%) PR‐19 HT displayed a DC electrical conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Fig. For instance, 15 dB g À1 cm 3 for polyethylene-carbon ber composites with 20 wt% (11 vol%) carbon ber loading, 61 35.3 dB g À1 cm 3 for reduced graphene oxide (rGO)/epoxy composites containing 2 wt% rGO, 62 and 500 dB g À1 cm 3 graphene/polydimethylsiloxane (PDMS) foams with 0.8 wt% (about 0.037 vol%) graphene loading 63 were achieved at 30 MHz to 1.5 GHz, respectively. Inset shows their specic SE at 200 MHz, 600 MHz, 1000 MHz and 9.6 GHz.…”
Section: Emi Shielding Performance Of Silver Nanollers/ Polyimide Comentioning
confidence: 99%
“…Fig. For instance, 15 dB g À1 cm 3 for polyethylene-carbon ber composites with 20 wt% (11 vol%) carbon ber loading, 61 35.3 dB g À1 cm 3 for reduced graphene oxide (rGO)/epoxy composites containing 2 wt% rGO, 62 and 500 dB g À1 cm 3 graphene/polydimethylsiloxane (PDMS) foams with 0.8 wt% (about 0.037 vol%) graphene loading 63 were achieved at 30 MHz to 1.5 GHz, respectively. Inset shows their specic SE at 200 MHz, 600 MHz, 1000 MHz and 9.6 GHz.…”
Section: Emi Shielding Performance Of Silver Nanollers/ Polyimide Comentioning
confidence: 99%
“…The intrinsic electrical conductivity of the modifier phase is an important factor in determining the electrical properties of the resulting composites . This conductivity, in turn, is a strong function of its graphitic crystallinity, which can be increased by heat‐treating the nanomodifiers to temperatures exceeding 2000°C as demonstrated in previous studies .…”
Section: Methodsmentioning
confidence: 76%
“…The assessment of graphitic crystallographic characteristics of carbonaceous materials can be primarily carried out by XRD . For graphitic carbon, X‐ray diffractograms display prominent peaks at about 26°, 42°, and 44° Bragg's angular positions (2θ) corresponding to reflections of the (002), (100), and (101) planes, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in cyclic butylene terephthalate/graphite/ carbon black composites, 8 the addition of CB increases the EMI SE of graphite/polybutylene terephthalate composites to 60 dB or so in the range of 30 MHz to 3 GHz. Villacorta et al 9 found that a treated carbon fiber-based polyethylene composite has a resistivity of 10 5 X cm and an EMI SE of 15 dB (30 MHz to 1.5 GHz). Gnidakouong et al 10 added multiwalled carbon nanotubes into unsaturated polyester and obtained a composite with an EMI SE above 20 dB in the range of 30-1.5 GHz.…”
Section: Introductionmentioning
confidence: 99%